TANGGAP WACANA DIALEK SUROBOYOAN: KOMPOSISI, TRANSMISI, DAN PERFORMANCE - Karyanto, Puji (ATAVISME, 2008)
The aim of this research is to identify the composruon, transmission. and performance of Tanggap Wacana Suroboyoan. In conducting the research. the writer uses descriptive-qua I ital ive method. The resu It of this research indicates that Tanggap Wacana Suroboyoan, presented in reception nuptials of Java subculture society. lapped over in a very flexible composition. There is no consistency and equality of composition among different pamedar sabda since they studied the Wacana Suroboyoan through few different methods, such as: autodidact, learning in courses institute. or learning from available books. In performance, pamedar sabda is trying to come up by using kromo inggil style of Surakarta Javanese. Nevertheless, they often fail to string up existing vocabularies between Indonesian dictions and Javanese ngoko from local dialect.